Denture care attitudes, hygiene levels and oral mucosal lesions in complete denture wearers from a single-institution cross‐sectional study - Büşra Tosun; Nur Uysal (Scientific Reports)
Abstract This study investigated denture care attitudes, dental visit habits, oral mucosal lesions, and hygiene levels in 118 complete denture users treated at a university dentistry faculty. Data on demographics, smoking, denture use duration, dentist visits, and hygiene habits were collected via a questionnaire. A specialist examined mucosal lesions and assessed denture hygiene level using the Budtz-Jorgensen and Bertram method. Categorical data were analyzed with Yates’s correction, Pearson’s chi-square, and Fisher–Freeman–Halton tests; multiple comparisons used the Bonferroni Corrected Z Test. Participants’ mean age was 51.61. Most were non-smokers (55.1%), visited dentists only for complaints (44.9%), cleaned dentures daily (70.3%), and removed them at night (56.8%). Good hygiene was observed in 40.68%. Females cleaned dentures more frequently than males, and 96.3% of those with poor hygiene reported bad denture odor. This study revealed significant deficiencies in denture care habits and inadequate hygiene practices of participants in a university dentistry faculty clinic. Most participants visited dentists only for complaints and had bad habits such as sleeping with their dentures at night and using inappropriate denture hygiene habits. Promoting proper denture hygiene habits and emphasizing the importance of regular dental visits can contribute to better oral health.